PERALIHAN HAK ATAS TANAH KAUM MENJADI TANAH HAK MILIK PERSEORANGAN DI KOTA BUKITTINGGI - , Khairulnas; , Agus Sudaryanto, S.H.,M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research entitled Transferring the right of clan land become individual ownership right land in Bukittinggi municipality aims to find out the process of transferring the right of clan land become individual ownership right land in Bukittinggi municipality and to find out the implication toward kinship relationship of individual ownership in Bukittinggi municipality. This research applies empirical law research which underlines primary data found from field research and secondary data as supporting data which consist of primary and secondary law materials. The research method is interview with instrument in form of interview guide. The literature research uses documentary study technique by using written law materials. The research subject is 10 (ten) informants. The data collecting technique is purposive sampling. The obtained data analyzed qualitatively. Based on the research can be found out that transferring process of clan land right become individual ownership right land in Bukittinggi municipality started through agreement of clan land transferring through trading